Drag Reduction In Two-Phase Oil-Water Flows With Polymeric Additives - Abdullah, M.Z. (2009)
In this work the effect of drag reducing polymers during oil-water flow was investigated experimentally. The studies were carried out in a horizontal 14-mm ID acrylic pipe. Exxsol D140 was used as the test oil (3.5 mPas, 828 kg/m3) while a polymer solution of partially hydrolyzed polyacrylamide (Magnafloc 1011) was added into the water stream (concentrations in the order of tenths of ppm) from an initially prepared more concentrated master solution (concentration in the order of hundred ppm). It was found that the concentration of the initial master solution as well as the period that was left to hydrate affected drag reduction; higher drag reduction was achieved with concentrated master solutions and short hydration times. The concentration of the polymer in the pipe also affected drag reduction but in this case a maximum was observed as concentration increased. Because of the small amounts of polymer used, the shear viscosity of the dilute polymer solutions in the pipe was very similar to that of water. However, the relaxation time that can be related to extensional viscosity was measured which indicated that increased extensional viscosities were associated with polymer solutions that gave the largest drag reduction.